Problematika Penyelesaian Sengketa Tanah Adat melalui Hukum Adat di Desa Lumban Ruhap, Kecamatan Habinsaran, Kabupaten Toba, Provinsi Sumatera Utara - Hotni Br Nainggolan; Rosnidar Sembiring; Maria (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The problematics of resolving customary land disputes through customary law in Lumban Ruhap Village, Habinsaran District, Toba Regency, North Sumatra Province, are characterized by legal uncertainty regarding the ownership of indigenous community land. These disputes are influenced by unclear legal status, indistinct land boundaries, population growth and increasing public legal awareness. Dispute resolution is carried out through customary deliberation mechanisms led by natua-tua ni huta, involving the disputing parties and the local community. However, in practice, several obstacles arise, including the absence of parties, lack of good faith to reach settlement, absence of witnesses, difficulties in obtaining valid evidence, as well as unclear land boundaries and ownership.